Global consumption of prescription opioid analgesics between 2009-2019: a country-level observational study. (December 2021) - Jayawardana, Sahan; Forman, Rebecca; Johnston-Webber, Charlotte; Campbell, Allen; Berterame, Stefano; de Joncheere, Cees; Aitken, Murray; Mossialos, Elias
Abstract: Background: Opioid analgesics play a key role in pain management but providing access while mitigating risk of misuse and dependence remains a challenge. Tracking global consumption of all opioids over time can help identify emerging patterns and drivers of use. Methods: Prescription opioid analgesic consumption was estimated for 76 countries between 2009 and 2019 using IQVIA MIDAS data. We reported country-level consumption trends in morphine milligram equivalents (MMEs), assessed differences in consumption between high-income (HICs), upper-middle income (UMICs), and low- and lower-middle income countries (LMICs), and identified country-level socioeconomic drivers of consumption using fixed-effects panel regression models. Findings: Global opioid consumption rate declined from 216·3 to 151·5 morphine milligram equivalents per 1, 000 inhabitants per day (MID) between 2009 and 2019, with consumption declines in the US and Germany. Overall, consumption rates increased in HICs by a median 36·6 MID (IQR, -7·5 -124·5) with substantial heterogeneity between countries. Median consumption rates were lower in UMICs (23·6 MID) and LMICs (8·3 MID) compared to HICs (345·1 MID) and increased by median 10·4 and 3·7 MID from 2009-2019, respectively. Consumption rates were associated with income (coefficient 18·84, 95% confidence interval 3·8-33·9) and trade (13·59, 1·3-25·8) in UMICs, and physician density (1·95, 1·2-2·7) in LMICs. Tramadol consumption rate increased in the study period and accounted for a relatively large proportion of total opioid volume consumed across all country-income groups. Interpretation: Substantial heterogeneity in global opioid consumption patterns reflect the challenges involved with providing adequate access to opioid treatment while avoiding potential misuse. Funding: This work was supported by LSE Health at the Department of Health Policy, London School of Economics. IQVIA did not fund this project.